2010
DOI: 10.1210/en.2010-0368
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of the Inflammatory and Stress Systems in a Hepatic Cell Line: Interactions between Glucocorticoid Receptor Agonists and Interleukin-6

Abstract: The liver plays an important role in inflammation and stress by producing the acute phase proteins (APPs) required for resolution of inflammation as well as by delivering systemic glucose, through gluconeogenesis, required to fuel the stress response. Disruption of the interplay between interleukin 6 (IL-6) and glucocorticoids (GCs), the peripheral mediators of inflammation and stress, respectively, may lead to side-effects associated with the pharmacological use of GCs. The current study investigated the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 84 publications
1
20
3
Order By: Relevance
“…Such findings would be in contrast with the lack of a consistent rise in TAT expression observed in our study in DEX‐administered bulls, although contradictory results concerning the parallelism between TAT induction and GR levels have also emerged in human (Duret et al. , 2006) or murine cell lines (Visser et al. , 2010).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Such findings would be in contrast with the lack of a consistent rise in TAT expression observed in our study in DEX‐administered bulls, although contradictory results concerning the parallelism between TAT induction and GR levels have also emerged in human (Duret et al. , 2006) or murine cell lines (Visser et al. , 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, it has been reported that veal calves or cattle treated with DEX at growth-promoting dosages exhibited little variation (Giantin et al, 2010) or even an increase in the amount of hepatic GR mRNA (Cantiello et al, 2009;Divari et al, 2011). Such findings would be in contrast with the lack of a consistent rise in TAT expression observed in our study in DEX-administered bulls, although contradictory results concerning the parallelism between TAT induction and GR levels have also emerged in human (Duret et al, 2006) or murine cell lines (Visser et al, 2010).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…GR is down-regulated in response to GC exposure in most tissues [20][23] and in some tissues down-regulation is linked to aging [24], [25], exercise [24] and psychological stress [26], [27], while up-regulation in some tissues is linked to HIV infection [28], muscle sepsis [9], dietary restriction [29], adrenalectomy [30] and cancer [10]. In addition, GR expression levels differ greatly between tissues [5], [31] and inter-individual variances are found within the same tissue type [8], [32].…”
Section: Introductionmentioning
confidence: 99%